The Machine. A Novella And How It Came To Be - Anton Sturla Antonsson 1991- (2014)
This assignment is written as a creative B.A. thesis at the University of Iceland and consists of two parts. The former is a novella of around 8,800 words called The Machine which I wrote in the autumn and winter of 2013 as my B.A. essay. It centers around a talented young man named John who aspires to be the greatest painter of his generation. Shy and withdrawn, he struggles through his daily life as an art student at a university where his superiority breeds jealousy in the other students. However, his destiny as an artist is seemingly halted when his only friend within the school suddenly begins to plagiarize his work. On top of this and unbeknown to John a serious and life-altering disease is growing within him and is already leaving its mark on him. With the help of the only two people he can trust he must battle the odds and prove himself as the great artist he knows he is. The story possesses traces of thriller and horror along with surrealistic elements and, hopefully, a dab of humor. However, categorizing it according to genre could be a tricky task as it was written without particular aims of that kind in mind, but was rather allowed to grow devoid of such worries. The latter part of this assignment is an exposition written in an attempt to shed light on the process behind the creation of The Machine and is around 3,700 words. It goes into detail about the conception of the story, its development, the research done for it and various other subjects. It is worth noting that anyone reading the exposition is expected to have read the novella beforehand.